Hubungan Pancasila dan Hukum Konstitusi : Implikasi Terhadap Pengakuan dan Perlindungan Hukum Adat di Indonesia (International Forum of Researchers and Lecturers, 2024)
This article discusses the relationship between Pancasila as the state ideology and constitutional law in Indonesia, particularly in the context of the recognition and protection of customary law. Using a normative juridical research method, the study examines the relevance of Pancasila in shaping the legal foundation and state policies that support the sustainability of customary law. The study also highlights the constitutional implications in providing formal recognition of the existence of customary law and the efforts to protect the rights of indigenous communities in Indonesia.The research findings indicate that Pancasila, as the state ideology, plays a crucial role in guiding constitutional law to protect local wisdom and cultural diversity, including in matters of customary law. Although the recognition of customary law has been accommodated within the constitution, its implementation still faces various challenges, particularly related to conflicts between customary law and national law. Therefore, synergy between Pancasila and constitutional law is needed to strengthen the protection of customary law within the framework of the Indonesian legal system.